β-Catenin Mediates Alteration in Cell Proliferation, Motility and Invasion of Prostate Cancer Cells by Differential Expression of E-Cadherin and Protein Kinase D1 - Syed, Viqar (2008)
We have previously demonstrated that Protein Kinase D1 (PKD1) interacts with E-cadherin and is associated with altered cell aggregation and motility in prostate cancer (PC). Because both PKD1 and E-cadherin are known to be dysregulated in PC, in this study we investigated the functional consequences of combined dysregulation of PKD1 and E-cadherin using a panel of human PC cell lines. Gainand loss of function studies were carried out by either transfecting PC cells with full-length E-cadherin and/or PKD1 cDNA or by protein silencing by siRNAs, respectively. We studied major malignant phenotypic characteristics including cell proliferation, motility, and invasion at the cellular level, which were corroborated with appropriate changes in representative molecular markers. Down regulation or ectopic expression of either E-cadherin or PKD1 significantly increased or decreased cell proliferation, motility, and invasion, respectively, and combined down regulation cumulatively influenced the effects. Loss of PKD1 or E-cadherin expression was associated with increased expression of the pro-survival molecular markers survivin, β-catenin, cyclin-D, and c-myc, whereas overexpression of PKD1 and/or E-cadherin resulted in an increase of caspases. The inhibitory effect of PKD1 and E-cadherin on cell proliferation was rescued by coexpression with β-catenin, suggesting that β-catenin mediates the effect of proliferation by PKD1 and E-cadherin. This study establishes the functional significance of combined dysregulation of PKD1 and E-cadherin in PC and that their effect on cell growth is mediated by β-catenin.